Analysis of nanomedicine primary tumor vs. metastasis targeting using clinical-stage core-crosslinked polymeric micelles - Larissa Yokota Rizzo; Federica De Lorenzi; Saskia von Stillfried; Seyed Mohammadali Dadfar; Qizhi Hu; Sanjay Tiwari; Claus-Christian Glüer; Marielle Thewissen; Felix Gremse; Stephan Rütten; Peter Boor; Wilhelm Jahnen-Dechent; et al. (Cell Reports)
Summary: Targeting and treating metastatic cancer remain major clinical challenges. We developed an optically imageable metastatic mouse model based on near-infrared protein-expressing 4T1 triple-negative breast cancer cells. Using multimodal imaging, we studied the tumor and metastasis tropism of core-crosslinked polymeric micelles (CCPMs) as well as the antitumor and antimetastatic efficacy of clinical-stage docetaxel-loaded CCPMs (docetaxel-CCPMs). We show that nanomedicines effectively target metastases, albeit with lower efficiency than primary tumors. Tumor microenvironment analysis revealed that metastases are more vascularized than primary tumors but also present with higher levels of collagen crosslinking, thereby hindering nanomedicine accumulation. A comparison of mouse and human tumors and metastases showed similarities and differences, consistently demonstrating increased vascularization in metastases. In mice, docetaxel-CCPMs outperformed standard docetaxel in terms of efficacy and toxicity. These findings underscore the potential of nanomedicine to improve metastatic cancer therapy, and they offer new insights into the tumor and metastasis microenvironment as a determinant of targeted drug delivery.